Barthélemy Aneau’s Alector ou le coq and the Paradox of Renaissance Cosmopolitanism - Meyer, Jenny (Renaissance and Reformation / Renaissance et Réforme, 2015)
Barthélemy Aneau’s histoire fabuleuse, Alector ou le coq (1560) epitomizes a burgeoning sixteenth-century awareness of the globe and its scope. New possibilities for envisioning global space went hand in hand with the development of cosmopolitan sympathies among Renaissance humanists; namely, enthusiasm for the ideal of a world republic. In this article, I show how Aneau’s fictional narrative demonstrates an idealized vision of the French monarch’s global role. I argue that Alector is written in the spirit of the princely manual, with a singular emphasis on the monarch’s obligatory mastery of spatial navigation that evinces sixteenth-century awareness of geography’s relevance to governance. Aneau creates a pastiche of French foundation myths and of geographical sources in order to emphasize both the French monarch’s preeminence and his worldwide reach. Elements of the hermetic tradition are manifest in Alector, where space is allegorized to illustrate Aneau’s conception of France’s place in the cosmos; in this way, his work is similar to that of his contemporary, the self-described cosmopolitan Guillaume Postel. Ultimately, there is a discord between the real geography evoked in Alector and the fictional genre that houses it. This dissonance emphasizes the paradoxical nature of a cosmopolitanism that strives to incorporate nationalism, and illustrates an unresolved complexity for would-be Renaissance world citizens.